Effect of source of carbohydrate and degradable intake protein in supplements on low-quality forage utilization by steers - Arroquy, J.I.; Cochran, R.C.; Wickersham, T.A.; Llewellyn, Donald A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve ruminally fistulated steers were used in an experiment to study the impact of the source of carbohydrate (CHO) and degradable intake protein (DIP) in supplements on low-quality forage utilization. Treatments consisted of two different CHO types (fed at 0.16% of initial BW) each offered with an equal amount of DIP (0.087% of initial BW) but with six different proportions of non-protein nitrogen (NPN) and true protein as sources of DIP. The CHO types were starch and dextrose (a simple sugar). The different proportions of the two sources of N contributing to the DIP were 100:0, 80:20, 60:40, 40:60, 20:80 and 0:100 % of supplemental N as casein (true protein source) vs urea (NPN source), respectively. Interactions were not evident for the traits presented. Forage OM, total OM, and total digestible OM intake increased in response to an increase in the proportion of supplemental true protein. Although CHO type did not affect intake, digestibility of OM and NDF was greater when the simple sugar rather than starch served as the CHO source.
Keywords: Beef; Forage; Starch; Sugar; Protein; Urea; DIP; Steers